The Influence of Health Insurance Sales Strategy, Corporate Branding, and Risk Management on the Decision to Choose BRI Life Products: The Mediating Role of Customer Satisfaction - Nuryanto, Nadya Ulfa Wardani; Chan, Syafrizal (International Journal of Social and Management Studies, 2026)
The purpose of this study is to examine and analyze the influence of health insurance sales strategies, corporate branding, and risk management on the decision to choose health insurance products, with customer satisfaction as a mediator. The research population for this study is BRI Life customers in the Jabodetabek area, with a total population of 9.90 million policies. The sample size is 119 respondents. The sampling technique used non-probability sampling with the purposive sampling method. The data analysis method used is the Partial Least Squares-Structural Equation Modeling (PLS-SEM) model. The research results indicate that health insurance sales strategy and corporate branding do not significantly affect customer satisfaction, while risk management does. Health insurance sales strategy and customer satisfaction significantly influence the decision to choose a product, but not corporate branding and risk management. Customer satisfaction does not significantly mediate the relationship between health insurance sales strategy and corporate branding, while it does for risk management.